Legal Protection Regarding Names and Visual Artists in the World of Writing from a Copyright Perspective (Journal of Creativity Student, 2020)
In this scientific article, the author will discuss the latest problems related to the world of fanfic genre authorship which is currently on the rise because of the rising prestige of world artists and more specifically related to the rise of the Korean entertainment industry as trendsetters in various sectors, especially for book lovers or who like to read books, Fanfiction works are now starting to run rampant on various social media platforms, namely the most talked about and the most impactful is blue bird social media or twitter, many new writers who produce fanfiction works based on artists or idols in the form of diverse writings, Idols and artists are used as visualizations and inspirations although sometimes the author also makes his own groove or character, when the writing rises to the top of trending and get a lot of attention then book publishers are now starting to glance at the existence of twitter fanfiction so that initially the fanfiction is only for entertainment then now it begins to be commercialized in the form of physical books. However, the problem that there are many authors and publishers do not pay attention to the ethics of doing business or the rules or laws that apply related to copyright and intellectual property rights reflected from promotion to the creation of physical books still associate the visuals and names of famous artists or idols so as to indirectly increase the price figure and the number of enthusiasts.